An Analysis of Senior High School Students’ Difficulties in Learning Historical Recount Text - Fidianingsih, Ambar; Muhtadi, Ali (Jurnal Pendidikan Progresif, 2021)
Abstract: An Analysis of Senior High School Students’ Difficulties in Learning Historical Recount Text. Objectives: This study described the senior high school students’ difficulties while learning historical recount text in English class and analyzed the causes of their difficulties. Methods: This study used a test, a questionnaire, and an interview. Findings: This study showed that 67% of students considered historical recount text as difficult materials. Students’ average score was 52.94 or below the minimum criteria of mastery learning. 23.5% of students passed the minimum criteria, while 76.5% of students did not pass it. Students’ difficulties in the “high” level of difficulty were about the social function, text structure, and main idea. Meanwhile, grammar features and arranging text had a “moderate” level of difficulty. The causes of these difficulties were the lack of vocabulary mastery, the lack of understanding about the concept of recount text, and the lack of grammar understanding. Conclusion: Students face difficulties in reading historical recount text materials due to the lack of English vocabulary mastery, grammar, and text concept. Keywords: English, reading, historical recount text, learning difficulties, senior high school. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202109